2007
DOI: 10.1111/j.1440-1681.2007.04792.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Tablets Reduce Osteoporosis Risk Factors and Increase Insulin‐like Growth Factor‐1 in Teenage Girls

Abstract: 1. The present study was conducted to examine whether supplementation of calcium (Ca) has a beneficial effect on bone mineral content (BMC) and bone mineral density (BMD).2. Healthy volunteer Japanese girls aged 15 -18 years were randomly assigned to two groups, one group taking Ca tablets (300 mg) and the other placebo tablets (Pt) (vehicle only) daily for 8 months, in a double-blind parallel placebo-controlled design.3. Eighteen girls completed the study (nine in each group). In the Ca group, BMC increased s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…it is some component in dairy products that is responsible for increasing serum concentrations of IGF-I because we showed no evidence for an association between the intake of protein or calcium from nondairy sources and IGF-I. Because there is only limited evidence to support an increase in IGF-I concentrations with calcium supplementation alone (35,43,44), we suggest that our finding of a positive association between calcium and IGF-I is unlikely to be due to calcium intake per se and could instead be due to another factor in dairy products, namely protein. Notwithstanding the positive association between dairy protein or calcium intake and IGF-I concentrations, and plausible biological mechanisms, the effect of reducing the consumption of milk or dairy, or calcium intake on concentrations of serum IGF-I and IGFBPs remains untested.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…it is some component in dairy products that is responsible for increasing serum concentrations of IGF-I because we showed no evidence for an association between the intake of protein or calcium from nondairy sources and IGF-I. Because there is only limited evidence to support an increase in IGF-I concentrations with calcium supplementation alone (35,43,44), we suggest that our finding of a positive association between calcium and IGF-I is unlikely to be due to calcium intake per se and could instead be due to another factor in dairy products, namely protein. Notwithstanding the positive association between dairy protein or calcium intake and IGF-I concentrations, and plausible biological mechanisms, the effect of reducing the consumption of milk or dairy, or calcium intake on concentrations of serum IGF-I and IGFBPs remains untested.…”
Section: Discussionmentioning
confidence: 55%
“…In the Nurses' Health Study, Holmes et al (11) found a positive relation between IGF-I concentrations and calcium from foods but there was little association if calcium from supplements was included. The most compelling evidence to support a role for dairy intake and elevated IGF-I concentrations lies with findings from intervention studies that show an increase in IGF-I in response to a higher intake of milk and dairy products in both younger (33)(34)(35) and older (36)(37)(38) participants.…”
Section: Discussionmentioning
confidence: 99%
“…In two of the trials, no effect of calcium supplementation on IGF-1 concentrations among postmenopausal women was found after follow-up periods of 6 months and 2 years 26,27. In a third trial among 18 Japanese teenage girls over 8 months, only within-treatment group changes in IGF-1 levels were reported 28. However, by our calculations, there was an estimated approximately 16% increase in IGF-1 levels in the calcium supplementation group relative to the placebo group.…”
mentioning
confidence: 94%